Geology today understanding our planet - Murck, Barbara Winifred 1954- (John Wiley & Sons, 1999)
This book provides an introduction to the six main areas of physical geography. It uses an earth systems approach to discuss the planet as a whole, plate tectonics, rocks and rock formation, surface processes, oceans/atmospheres, and resources.